Prediksi Kesulitan Keuangan Terhadap Manajemen Laba: Berdasarkan Analisis EM Score - Kodriyah, Kodriyah; Mahardini, Nikke Yusnita; Umdiana, Nana; Sudrajat, Ajat (Universitas Muhammadiyah Metro, 2023)
Government policies in combating the Covid-19 pandemic have an impact on the business world, especially the hotel, restaurant, and tourism sectors, this causes the company's cash flow to decrease, while obligations must still be paid by the company, this condition can cause the company to experience financial difficulties and is predicted to go bankrupt. This situation can be a loophole for managers to take opportunistic actions to process profits so that their performance still looks good in the eyes of the principal for their interests. This study aims to predict the company's financial difficulties during the Covid-19 pandemic and how it affects profit management carried out by managers. The method used in this study is simple regression by being processed using the help of SPSS. The result obtained is that when the company experiences financial distress, it can influence management to carry out profit management actions.